2016
DOI: 10.1039/c6ra21768k
|View full text |Cite
|
Sign up to set email alerts
|

A bright yellow light from a Yb3+,Er3+-co-doped Y2SiO5upconversion luminescence material

Abstract: A bright yellow light from Yb3+and Er3+doped Y2SiO5upconversion materials in particle and fiber form were prepared by a co-precipitation, and electrospinning method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…(b)). The mechanism of this process can be found elsewhere . On the contrary, these peaks were not observed for the TiO 2 , and TiO 2 –Ce 0.14 samples.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…(b)). The mechanism of this process can be found elsewhere . On the contrary, these peaks were not observed for the TiO 2 , and TiO 2 –Ce 0.14 samples.…”
Section: Resultsmentioning
confidence: 81%
“…In the case of TiO 2 –Er 0.15 Yb 0.15 and TiO 2 –Er 0.15 Yb 0.15 Ce 0.14 , the bands at 522 and 655 nm relate with 4 I 15/2 → 4 F 7/2 , 4 I 15/2 → 2 H 11/2 and 4 I 15/2 → 4 F 9/2 transitions of Er 3+ . The broad band at 982 nm originates from 2 F 7/2 → 2 F 5/2 transition of Yb 3+ . The appearance of these bands exhibited that Yb 3+ and Er 3+ have been successfully incorporated in TiO 2 .…”
Section: Resultsmentioning
confidence: 95%
“…Notice that, after heat treatment at 1050 °C, the absorption peaks associated with the organic compounds (∼1250–1700 cm –1 ) are significantly suppressed. On the other hand, the bands at 1017 cm –1 , 956, 870, and 489 cm –1 are attributed to the Si–O–Si antisymmetric and symmetric stretching vibrations of the silicate (SiO 4 ) group. , Finally, the lowest energy bands, centered at 560, 636, and 717 cm –1 , are associated with vibrational modes related to Y–O coupling. , The room-temperature Raman spectrum of the heat-treated Y 2 SiO 5 :Tb 3+ powder, annealed at 1050 °C, in the range of 400–1100 cm –1 is shown in Figure . It is observed that the sample shows vibrational modes from 450 to 1100 cm –1 , characteristic to the Y 2 SiO 5 structure.…”
Section: Synthesis and Sample Characterizationmentioning
confidence: 99%
“…The selection of the RE host is vital for getting an efficient UC and among the materials of interest, oxy-orthosilicate (Y 2 SiO 5 ) appears as appropriate host matrix for UC. Many authors demonstrated already that Y 2 SiO 5 exhibits excellent thermal and chemical properties and large PL properties when doped with RE ions. …”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the spectroscopy of lanthanide (Ln) ions doped oxide and fluoride crystals is an interesting research subject because of abundant applications of such materials [1][2][3][4][5]. In the comparison with oxide crystals, the fluoride crystals have been shown to have more advantages such as: (i) large band gap yielding the emission from the high energy levels of Ln ions; (ii) weak nephelauxetic effect and a moderate crystal-field strength generating the narrow emission bands as well as a long lifetime of excited levels within 4f electron configuration and (iii) low phonon energy leading to a high quantum efficiency of luminescence from some excited levels [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%